Particle size characteristics of sliding-zone soil and its role in landslide occurrence: a case study of the Lanniqing landslide in Southwest China - Xu, Zongheng; Ye, Hongchen; Li, Lingxu (Frontiers in Earth Science, 2024)
In landslide studies, particle size is a key quantitative indicator, reflecting the formation and development of the sliding zone. It plays a crucial role in understanding the mechanisms and evolutionary processes that lead to landslide occurrences. Precise measurement of particle size is crucial. This study centered on soil samples from the Lanniqing landslide in Southwest China. To begin, seven distinct methods were used to preprocess the soil samples. Next, the particle size frequency distribution was measured using the Mastersizer 2000 laser particle size analyzer. Key parameters, including median particle size, mean particle size, sorting coefficient, skewness, and kurtosis, were then compared and analyzed to determine the most appropriate preprocessing method for evaluating the characteristics of the soil samples. The mechanism of landslide occurrence was subsequently analyzed by examining the particle size characteristics, mechanical properties, and mineral composition of the soil samples. The results suggested that method C provides the most reliable analysis of particle size characteristics in soil samples. The observed coarsening of coarse particles, along with a significant increase in clay content within the sliding zone, indicates that the sliding surface has undergone multiple shear and compression events. The interplay of the upper traffic load and slope cutting at the front edge set the stage for the Lanniqing landslide, prompting the initial development of potential sliding surfaces. Rainfall acts as a catalyst for slope instability. The high clay content, combined with the formation of a low-permeability layer rich in clay minerals on the sliding surface, leads to excessive pore water pressure and mineral lubrication. These factors inherently trigger and accelerate the occurrence of the landslide.